Health (including Clinical Studies) - Bertram Häussler; Elke Hempel (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Politics, science, research and the public base their discussions on comprehensive, valid and systematic health care data. Data based information is needed in order to measure the results or success of a policy of procedure. In Germany, the Information System of the Federal Health Monitoring (IS-GBE) comprises of a comprehensive health system data collection. Currently, the information system contains health data and information from over a 100 different sources, for instance surveys done by the statistical offices of the federation or the Länder, as well as many other surveys done within the health care system. Apart from the IS-GBE additional official and non-official health care data sources exist in Germany. Within this expertise changes made from 2001 on to existing health data sources as well as newly established data sources are presented. Data sources dealt with in other expertise are not considered. The up until now one time insuree sample collected in 2001 was, for example, collected in the course of the reform of the risk structure adjustment within the statutory health insurance is one of the more recent samples. From our point of view we highly recommend an update of this representative sample.
Keywords: 330; Information System of the Federal Health Monitoring (IS-FHM); Microcensus; Inpatient Diagnosis Data; Hospital statistics by Diagnosis Related Groups (DRG Statistics); Cancer Registries; Kidney Replacement Therapy Statistics (QuaSi Niere); External Comparative Quality Assurance of the In-patient Sector (BQS); Structured Reports on Quality (SQB); Compulsory Health Insurance (CHI) Claims Data: Insuree Sample; GEK Claims Data